Parkinson's disease dementia and dementia with lewy bodies differences and similarities - Joanna Krasowska; Johan Lökk (Open Journal of Parkinson's Disease and Treatment - Peertechz Publications, 2023)
The second most common neurodegenerative disease causing dementia in the population over 65 years is Parkinson´s Disease Dementia (PDD), sharing many clinical, genetic, pathophysiological, imaging, and morphological features with Dementia with Lewy Bodies (DLB). There is an ongoing debate whether these two diseases are separate diseases, just different phenotypes on the basis of the same Lewy Body pathology or the same disease. The differences are rather few and many authors tend to believe that PDD and DLB may be manifestations of the same neurodegenerative disorder. Based on a single examination, without regard to the temporal sequence of events, it is difﬁcult or impossible to differentiate a single patient with parkinsonism as PDD or DLB. The relative timing when cognitive and motor symptoms appear, applying the 1-year rule, could be helpful in clinical practice in distinguishing the diseases. The subtle differences are hard to observe with more executive problems in PDD and a tendency of more easily triggered psychotic problems in DLB. Eventually, PDD and DLB might be the same disease - as long as unquestionable biomarkers definitely distinguishing both entities are not found.